The Role of the CJEU in Ensuring Migrants’ Security – Analysis of the Post-Crisis Case-Law - Kosińska, Anna Magdalena (Review of European and Comparative Law, 2019)
The current article presents the findings of the research on the case-law of the CJEU in the area of asylum and return migration law concerning protection of migrants’ rights. The analyzed case-law concerns the proceedings from the period after the escalation of the European migration crisis in April 2015. The presented study seeks to answer the question about the existence of a juridical standard for the protection of the right to migration security. The analysis also includes the examination of the relation between the necessity of providing security in migration processes and the obligation to ensure the protection of migrants’ fundamental rights.